ANALISA DAN PENGEMBANGAN TATA KELOLA TEKNOLOGI INFORMASI (IT GOVERNANCE) MENGGUNAKAN COBIT 5 - Anita Febriani (STMIK Hang Tuah Pekanbaru, 2017)
Success in providing information services can provide a positive impact to the organization that is in accordance with the expectations of stakeholders. Therefore, the application of IT governance, especially for academic information systems need to be monitored and evaluated to ensure that the entire mechanism of IT management goes according to plan, objectives and business processes. The evaluation also should not only be done in the early stages of a system implemented, but should also be done regularly. The methodology in this study using the COBIT 5 framework that begins with those identified and mapped to the COBIT 5 processes selected. We then measured against these processes to determine the level of the current process capability and also carried out targeting the expected level of capability. Process capability level gap analysis of current and expected conducted to determine the extent to which improvements should be made to these processes. Recommendations for improvement of these processes is based on the COBIT framework 5. Results of this research is assessment and targeting capability level 5 COBIT 5 process were selected as well as recommendations for improvement of IT services activities.